Dielectric and ionic transport properties of bio-based polyurethane acrylate solid polymer electrolyte for application in electrochemical devices - Tuan Naiwi, Tuan Syarifah Rossyidah; Min, Min Aung; Rayung, Marwah; Ahmad, Azizan; Kai, Ling Chai; Lee, Mark Wun Fui; Mohd Tarmizi, Emma Ziezie; Abdul Aziz, Nor Azah (Elservier, 2022)
Solid polymer electrolyte has been extensively studied as an alternative to liquid electrolyte that is often affected by the leakage, deformation and limited range of operating temperature issues. The present study was conducted in an attempt to synthesize polyurethane acrylate (PUA) as a host polymer to evaluate polymer performance supplemented with Li salt as polymer electrolytes. PUA was prepared by the reaction of jatropha oil polyol with toluene 2,4-diisocyanate and hydroxylethylmethylacrylate. Lithium perchlorate (LiClO4) salt with different percentage of weight in the range of 5 wt. % to 25 wt. % was added to PUA to produce the PUA electrolyte. The mixtures were cured under UV radiation to obtain thin polymeric films with good thermal stability and ionic conductivity. PUA with 25 wt. % lithium salt has the highest conductivity of 6.40 × 10−5 S cm−1 at room temperature. The finding was supported by Fourier transform infrared (FTIR). Electrode polarization occurrence was interpreted by the complex dielectric constant (Ɛr), dielectric loss (Ɛi), real electrical modulus (Mr), imaginary electrical modulus (Mi) and tan σ. The effect of lithium salt addition was investigated by differential scanning calorimeter (DSC), thermogravimetric analysis (TGA), X-ray diffraction (XRD) and scanning electron microscopy (SEM) analyses. Additionally, the ionic transport properties, transference number measurement and electrochemical stability were presented.